NONLINEAR CURVE FITTING METHOD DEVELOPMENT FOR EXTRACTION MODAL PARAMETERS OF FREQUENCY RESPONSE FUNCTION VISCOUS DAMPING - SUPRIYATNA (NIM : 131 07 017); Pembimbing Utama : Prof. Dr. Ir. Komang Bagiasna, YANA
Dynamic characteristics have a significant influence to the mechanical structure. Modal parameters of the mechanical structure is part of the dynamic characteristics that have been widely studied. These methods have been widely carried out to obtain the modal parameters structure of the vibration. One method to obtain modal vibration parameters is the curve fitting method. This method is a process of forming a curve or a mathematical model that has the best fit to a series of measurement data points (data points). In this research, an analysis of modal parameters which include the use of these characteristics to formulate a mathematical model of dynamic behavior of a mechanical structure. This analysis comes with a Matlab program as a form of implementation of mathematical models of dynamic behavior. In a mathematical modeling performed analytical explanation for the case of nonlinear functions. Adjustment of the mathematical model with the results of testing are the basic steps in determining modal parameters of structures. Response curve of the test results FRF extracted as a reference for adjusting the mathematical model. Likewise with the response curve generated from mathematical models. Numerical analysis is done to complete the model by using Matlab, which the vibration equation simulated in the form of vibrations which is a response curve of vibration in the frequency domain. This modeling curve is a curve fitting method for extracting the required parameters of a mechanical structure. The results of mathematical modeling (curve fitting) has resulted parameter extraction method in modal mechanical structure for response in the frequency domain. Based on the results of these parameters are expected to identify the vibration problems that exist today.